2018
DOI: 10.1097/jnn.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auditory Stimulation on the Level of Consciousness in Comatose Patients Admitted to the Intensive Care Unit: A Randomized Controlled Trial

Abstract: Background: Comatose patients are exposed to sensory deprivation in the intensive care units. Auditory stimulation of patients who are unconscious is a nonmedical procedure. This study examines the effect of organized voice, performed by a nurse, on the state of consciousness of comatose patients in intensive care units. Method: This randomized controlled trial study of 60 patients was conducted fitting between August 2017 and February 2018. For 10 days, patients received the voice of a male nurse twice a day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Additionally, Sun and Chen (2015) [53] study to assess the role of music therapy on LOC among severe TBI patients revealed that the LOC were significantly higher in the music group compared to the control group. Similarly, Cevik and Namik (2018) [54] reported significant increase in the mean values of GCS among comatose patients after auditory stimulation application in comparison with GCS of patients in the control group.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, Sun and Chen (2015) [53] study to assess the role of music therapy on LOC among severe TBI patients revealed that the LOC were significantly higher in the music group compared to the control group. Similarly, Cevik and Namik (2018) [54] reported significant increase in the mean values of GCS among comatose patients after auditory stimulation application in comparison with GCS of patients in the control group.…”
Section: Discussionmentioning
confidence: 82%
“… 8 10 Studies show that physical or virtual visits of family members to ICU patients reduce the incidence of anxiety, depression, 8 , 11 confusion, agitation, and delirium, 12 promote oxygen saturation, 7 and result increase in the Glasgow Coma Scale (GCS) score. 4 These studies agree that visits, real or virtual, increase the satisfaction of patients and family members. 12 , 13 Mohammadi et al determined that organized auditory stimulation by a familiar voice affects BP, body temperature, and consciousness level in patients admitted to the ICU and recommended habitual use of this application.…”
Section: Introductionmentioning
confidence: 79%
“… 2 , 3 Patients experience stress and anxiety for reasons that include sensory deprivation, sensory overload, invasive procedures, excessive environmental stimuli, lack of social support systems, and an unfamiliar environment. 4 , 5 Stress can alter patients’ body temperature, cardiac contractility and output, blood pressure (BP), pulse rate (PR), respiratory rate (RR), and oxygen saturation (SpO 2 ). 1 , 3 , 6 , 7 Pharmacological and nonpharmacological methods are used to reduce these problems in ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…[16,23,24] Kevic K and Namic E (2018) found that GCS becomes higher with the application of auditory stimulation in comatose patients. [30] Pape et al study, 2015 examined the effects of auditory stimulation program on level of consciousness of acute traumatic brain injured patients. They found that there is an improvement in neurobehavioral performance in the study group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%